2005
DOI: 10.1128/aem.71.11.6590-6599.2005
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interspecific Comparisons of Bacterial Diversity and Community Structure Support Coevolution of Gut Microbiota and Termite Host

Abstract: We investigated the bacterial gut microbiota from 32 colonies of wood-feeding termites, comprising four Microcerotermes species (Termitidae) and four Reticulitermes species (Rhinotermitidae), using terminal restriction fragment length polymorphism analysis and clonal analysis of 16S rRNA. The obtained molecular community profiles were compared statistically between individuals, colonies, locations, and species of termites. Both analyses revealed that the bacterial community structure was remarkably similar wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
272
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(297 citation statements)
references
References 49 publications
21
272
1
Order By: Relevance
“…For this strong correlation between host phylogeny and microbial community composition, the term "phylosymbiotic microbiota" was recently introduced (33). Our observation is consistent with similar findings in insects (34,35) and mammals, including a detailed survey of the gut microbiota in hominid species (3,36). The observed associations in Hydra are extremely stable, as the analyzed species are cultivated under identical environmental conditions for up to 30 y.…”
Section: Discussionsupporting
confidence: 75%
“…For this strong correlation between host phylogeny and microbial community composition, the term "phylosymbiotic microbiota" was recently introduced (33). Our observation is consistent with similar findings in insects (34,35) and mammals, including a detailed survey of the gut microbiota in hominid species (3,36). The observed associations in Hydra are extremely stable, as the analyzed species are cultivated under identical environmental conditions for up to 30 y.…”
Section: Discussionsupporting
confidence: 75%
“…In this respect, Drosophila appears to parallel mammals, for which no phylogenetic pattern in the composition of the gut microbiota has been found (Ley et al, 2008a;Muegge et al, 2011). Our results differ from the evidence for congruence between host phylogeny and gut microbiota composition obtained, for example, for bacterial community composition in laboratory cultures of jewel wasps Nasonia (Brucker and Bordenstein, 2012), and wild populations of both great apes/humans and termites (Hongoh et al, 2005); and the genotypes of one bacterial species, Lactobacillus reuteri, in studies that included inbred lab mice and rats (Oh et al, 2010;Frese et al, 2011). An important issue for future work is the ecological factors that dictate the variation in the congruence of host-microbiota phylogenies across different animal groups.…”
Section: Discussioncontrasting
confidence: 56%
“…In this study, RDA analysis, response ratio, and correlation analysis suggested that members of phyla Spirochaetes, Fibrobacteres, as well as Firmicutes may be the main substrates degraders, e.g., straw-attached TG3 (one candidate class of the phylum Fibrobacteres), and those genera significantly increased at peaks I and II. The TG3 bacteria were mainly found in rumen and wood-feeding termite gut (Hongoh et al 2005;Hongoh et al 2006;Hess et al 2011), which are efficient in transforming plant polymers into sugars and VFAs. Thus, the prevalence of these bacteria associated to straw indicated their dominant roles in the breakdown of plant polymers and supplying soluble substrates for the fermentation and methanogenesis occurring in the slurry.…”
Section: Discussionmentioning
confidence: 99%